KAJIAN PROYEKSI PRODUKSI dan DAYA SAING KOMODITAS PERKEBUNAN dan PERTANIAN KABUPATEN JEMBER dalam MENDUKUNG POTENSI EKSPOR - Murwanti, Retno; Nurul Fathiyah F (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The growth of the agricultural and plantation sectors in Jember Regency plays an important role in the local economy, particularly in providing commodities with high export potential. Along with the development of global market demand, managing production, stock availability and increasing the competitiveness of commodities are key to strengthening Jember's position in the international market. Maintaining productivity and improving the competitiveness of export products requires in-depth projection analysis. This research aims to project the production and stocks of plantation and agricultural commodities in Jember Regency for the period 2024-2026, and to map their competitiveness and export potential. The problem of this research is to project the production and stocks of plantation and agricultural commodities in Jember Regency in 2024-2026, and to map the competitiveness and export potential of these commodities. The method used in this research is quantitative descriptive method with production projection approach using trend analysis and competitiveness calculation using Revealed Comparative Advantage (RCA). Data were obtained from relevant agencies and official publications and then analysed to describe the production potential and comparative advantage of the main commodities of Jember Regency. The results show that several plantation and agricultural commodities have stable projected production increases over the period 2024-2026. Certain commodities such as tobacco, coffee and cocoa show high competitiveness and significant export potential based on RCA values. These results suggest that sustainable production management and competitiveness improvement strategies are needed to maximise export potential. The results of this study are expected to serve as a basis for local government and stakeholders in designing export development policies for Jember's leading commodities in the international market.